Synthesis and Antibacterial Properties of Fluorapatite and FAp-ZnO-Chitosan Composite as Dental Implant Materials - Charlena; Khofiyatuzziyadah, Alif Aryan; Akhiruddin; Purwantiningsih (Science and Technology Indonesia, 2025)
Regenerative biomaterials research has continued to grow in recent decades, one of which is dental implants. The material that can be used is fluorapatite (FAp), as it is a significant element of human bones and teeth. FAp has better chemical and thermal stability than other apatite materials. However, FAp has low antibacterial properties, so it needs to be composited with other antibacterial materials, such as zinc oxide (ZnO) and chitosan. In addition, chitosan was also added to stabilize FAp and ZnO an effort to increase antibacterial and in vitro bioactivity in apatite formation. Therefore, this research intends to synthesize and assess the antibacterial properties and in vitro bioactivity of FAp-ZnO chitosan to increase its potential as a dental implant manufacturing material. FAp and ZnO were synthesized and then composited with chitosan into FAp-ZnO-chitosan by a simple mixing method. The FAp-ZnO-chitosan composite was successfully synthesized by looking at X-ray diffraction (XRD), Fourier Transform Infra-Red (FTIR), and Scanning Electron Microscope-Energy Dispersive X-ray (SEM EDX) characterization results. The in vitro bioactivity of the composite showed new surface growth during immersion with simulated body fluid (SBF) solution, indicating potential attachment of the implant material to the tissue. The antibacterial properties of FAp-ZnO-chitosan also showed an increased zone of inhibition compared to the single material. This indicates that the FAp-ZnO-chitosan composite material has the potential to be used as a dental implant material.